Respuesta :
Evaluate the expression using x = –1 and y=3.
[tex](6x^4y^3)[/tex]
1. Substitute the values for the variables.
we plug in -1 for x and 3 for y
[tex](6x^4y^3)[/tex]
[tex](6(-1)^4(3)^3)[/tex]
2. Identify grouping symbols, beginning with the innermost symbols.
[tex](6*(-1)^4*(3)^3)[/tex]
We take exponent and then we multiply
3. Determine and apply the rules of exponents to simplify
[tex](6*(-1)^4*(3)^3)[/tex]
(-1)^4 = -1 * -1 * -1 * -1 = 1
(3)^3 = 3*3*3= 27
[tex](6*(1)*(27))[/tex]
4. Evaluate.
[tex](6*(1)*(27))[/tex]
162
The value of the expression is 162
Using the principle of substitution, the value of the expression given is 162.
Given the expression :
- 6x⁴y³
x = -1 ; y = 3
Substituting the values into the expression :
6(-1)⁴(3)³
- -1⁴ = - 1 × - 1 × - 1 × - 1 = 1
- 3³ = 3 × 3 × 3 = 27
6(1)(27) = 6 × 1 × 27 = 162
Hence, the value of the expression is 162.
Learn more : https://brainly.com/question/25669152